Social innovation in the food village program as a CSR initiative in supporting food sovereignty PT. Pertamina International Refinery RU III, Plaju - Ika Bayu Kartikasari; Siti Rachmi Indahsari; Ahmad Adi Suhendra; Rully Mufarika (International Journal Labs, 2024)
This study aims to explain in a descriptive manner the social innovation of Pertamina International Refinery RU III, Plaju, in overcoming social problems in Plaju Ulu by realizing sustainable social development through the Innovative Food Village Program. The research employed a qualitative approach aimed at obtaining a comprehensive understanding of the social phenomena occurring within the community. The data analysis was conducted through descriptive analysis, organizing and categorizing data to form a systematic, detailed narrative. To enhance data credibility, a triangulation technique was applied to support the findings and validate the innovative food village program based on the literature reviewed in this study. The innovation of the innovative Food Village program is able to produce changes in the system chain and produce new derivative programs in the community that lead to community independence. Additionally, analyzing the long-term effects of knowledge transfer by Community Development Officers (CDOs) could provide insights into how mentorship and training contribute to sustained community engagement and self-sufficiency.